REL01: Online interview with an imam priest about sex educationa and school pregnancies (Health Discourses as Moral Communication? Linguistic Case Studies from Côte d'Ivoire and Cameroon)
Onlline interview with an imam priest about sex educationa and school pregnancies.
Keywords: Communication; Ethics; Women; Pregnancy; Reproductive health; Africa; Teenage pregnancy; Abortion; Contraception; Prevention; Applied ethics; Islam; Birth Control; Moral Communication; Imam; Côte d'Ivoire; Ivory Coast; Adolescent Pregnancy; Morality